Mapping and measuring the troposphere pollutants originated from the 1997 forest fire in South East Asia - Hashim, Mazlan; Kanniah, Kasturi; Rasib, Abd. Wahid; Lim, Chee Ming (Asian Association on Remote Sesning, 2001)
The massive forest fire in Indonesia in 1997 affected the whole Asian region by transporting large quantity of smoke plume with Malaysia bearing the brunt due to being nearer, wind direction and weather conditions. In this study, AVHRR (Advanced Very High Resolution Radiometer) satellite data were used to detect and subsequently map the five primary sources of fire pollutants namely Carbon monoxide (CM), Sulphur dioxide (SO2), Nitrogen dioxide (NO2), Ozone (O3) and particulate matter less than 10 micron ((PM10) in Peninsular Malaysia. A multi regression analysis was used in this study to establish a statistical relationship between atmospheric pollutants (ppm) readings recorded at 5 stations around the Peninsular and reflectance values from AVHRR data. This model, based on 5 samples was then applied to all the pixels in the image covering the whole Peninsular Malaysia. The obtained values are in parts per million (ppm) for all the constituents except for PM10 in ug/cu.m.